Efecto del consumo de linaza en el perfil lipídico, el control del cáncer y como terapia de reemplazo hormonal en la menopausia : una revisión sistemática de ensayos clínicos aleatorizados (2011)
ABSTRACT: To evaluate the effects of flaxseed consumption in changing the lipid profile, cancer control and hormone replacement therapy at menopause and andropause in individuals of all ages. Materials and methods: We conducted a systematic review of randomized controlled trials that examined the effects of flaxseed consumption on body weight reduction, change in blood lipid levels, cancer control and menopausal symptoms. We used Pub-Med, Lilacs, the libraries of PAHO and WHO, and clinical trials published in Cochrane between January 1, 2000 and June 30, 2010. The articles that met the inclusion criteria were assessed for methodological quality. Results: We included 49 articles. Studies reported that flaxseed consumption generates small changes in blood lipid concentrations, improvement in menopausal symptoms, promotes the reduction of tumor proliferation rates and increased apoptosis in breast and prostate cancer Conclusions: The results are not yet sufficient to recommend the use of flaxseed for the control of hypercholesterolemia in patients with dyslipidemia. The evidence favors flaxseed as an alternative adjuvant therapy for breast and prostate cancer treatment, and reduction of menopause symptoms.